The French Queen's Letters: Mary Tudor Brandon and the Politics of Marriage in Sixteenth-Century Europe. - WATKINS, JOHN (Early Modern Women: An Interdisciplinary Journal)
The article reviews the book "The French Queen’s Letters: Mary Tudor Brandon and the Politics of Marriage in Sixteenth-Century Europe," by Erin A. Sadlack, part of the book series entitled "Queenship and Power Series."